Epidemiology of subcutaneous mycoses in northeast India: A retrospective study - Shikha Verma; Binod Kumar Thakur; Vandana Raphael; Devinder Mohan Thappa (Wolters Kluwer Medknow Publications, 2018)
Background: Subcutaneous mycoses, although rare, are frequently reported from northeast India. Their spectrum varies with geographic region. Materials and Methods: We evaluated clinical records and histopathological features of subcutaneous mycoses cases seen during April 2013 to March 2017. Results: A total of 70 patients (44 males and 26 females) of subcutaneous mycoses were analyzed. Sixty-one percent of patients were 20-60 years old. Duration of the disease ranged from 3 months to 25 years. Most common site of involvement was the lower limb (32, 46%), followed by the upper limb (25, 36%). A history of trauma was obtained from 76% of patients. Eighty-seven percent of patients were from rural area. Ninety-two percent of patients were agricultural workers. There were 30 established cases of chromoblastomycosis and 16 cases of sporotrichosis. In 24 cases, subcutaneous mycosis was suspected clinically and showed some improvement to empirical itraconazole therapy. Multifocal lesions were seen in six patients. Complication of subcutaneous mycoses in the form of invasive squamous cell carcinoma was seen in one patient. On histopathological examination, verrucous hyperplasia was seen in 93% of cases. Granulomas with suppuration were seen in 77% of cases and granulomas without suppuration were seen in 14.3% of cases. Copper penny bodies were appreciated in 42.8% of cases. Fungal culture was positive only in 55.7% of cases. There was growth of Sporothrix schenckii in 16 patients, Fonsecaea sp. in 19, Cladosporium sp. in 3, and Curvularia sp. in 1. Conclusion: Chromoblastomycosis was the most common subcutaneous mycoses seen in northeast India followed by sporotrichosis. The diagnosis remained a challenge in a few cases as the culture positivity was very low. Suppurative granulomas in histopathology played a corroborative role. Therapeutic trial of itraconazole for 2 months was worth trying in such cases.